Pasang Surut Panggilan Jiwa Walikota Terpilih Kota Sungai Penuh: Seorang Entrepreneur yang tidak Berlatar Belakang Politik - Azani, Gandhi Wira; Fikry, Zulian (Indo-MathEdu Intellectuals Journal, 2025)
Becoming a successful entrepreneur is a highly coveted achievement, as the profession offers independence, financial stability, and room for growth. However, an interesting phenomenon arises when an established entrepreneur chooses to step out of their comfort zone and enter the world of politics. This situation raises questions about the factors that drive such a career change. This study aims to examine the political motivations of the elected mayor of Sungai Penuh City and to understand the reasons that led him to leave the comfort of his previous profession to enter the political arena. This study uses a qualitative research method with a phenomenological approach and uses data analysis techniques according to Miles, Huberman & Saldana, which consists of 3 stages, namely data condensation, data presentation, and conclusion drawing. Data collection for this study was carried out in 3 in-depth interview sessions with the elected mayor of Sungai Penuh. This study found three major themes consisting of several sub-themes. The first major theme is competence, which consists of experience and skills. The second is calling, which includes social support, altruism, achievement motivation, and self-confidence. The third is self-sacrifice, which consists of resilience, values, emotional regulation, integrity, strategy, challenge, problem solving, and role conflict.